(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
The constant comparison to others on social media can create a sense of inadequacy and dissatisfaction with one’s own life, leading to a negative impact on mental health. Moreover, social media can also create a false sense of reality, where users showcase only the positive aspects of their lives, hiding the struggles and challenges they face. This can lead to the creation of unrealistic expectations and a distorted perception of reality, which can negatively affect one’s mental health. While social media has its benefits, it is important to be mindful of its impact on our mental health. It is essential to use it in moderation and be aware of the negative effects it can have on our psychology. We should aim to maintain a balance between the virtual world and the real world, and strive to live a life that is authentic and true to ourselves, rather than one that is based on the illusions created on social media. Firstly, the impact of social media on mental health, including the issues of envy, comparison, and the creation of unrealistic expectations. Secondly, the potential revenue-generation aspect of social media through pay-per-click models, which can lead to the creation of mindless content and the exploitation of user attention. It is important to address both of these aspects and strive for a balance that promotes mental well-being while also utilizing the potential of social media for positive purposes. By being aware of the negative impacts and consciously working to mitigate them, we can create a healthier relationship with social media that benefits both individuals and society as a whole. This chapter analyses social media can provide a variety of benefits for individuals in the age bracket of 25 to 35, it is important to note that it should not be used as a replacement for professional mental health care. However, social media can be used as a tool to help individuals manage depression and improve their mental health in several ways.